2022
DOI: 10.1155/2022/1091042
|View full text |Cite|
|
Sign up to set email alerts
|

PTPN18 Stimulates the Development of Ovarian Cancer by Activating the PI3K/AKT Signaling

Abstract: Objective. To illustrate the functions of protein tyrosine phosphatase nonreceptor type 18 (PTPN18) in the progression of ovarian cancer and the potential molecular mechanism. Methods. Differential PTPN18 expression in ovarian cancer samples was determined. Following PTPN18 knockdown, changes in proliferation and migration in ovarian cancer cells were detected. Nude mice with ovarian cancer were used to uncover the effects of PTPN18 on ovarian cancer growth in vivo. Results. PTPN18 was significantly upregulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Strikingly, PTPN3 confers chemoresistance and tumor stem cell-like characteristics to ovarian cancer cells ( 82 ). Furthermore, PTPN11 and PTPN18 potentiate ovarian cancer invasion and metastasis through activation of PI3K/AKT axis ( 83 , 84 ).…”
Section: Role Of Ptpns In the Context Of Cancermentioning
confidence: 99%
“…Strikingly, PTPN3 confers chemoresistance and tumor stem cell-like characteristics to ovarian cancer cells ( 82 ). Furthermore, PTPN11 and PTPN18 potentiate ovarian cancer invasion and metastasis through activation of PI3K/AKT axis ( 83 , 84 ).…”
Section: Role Of Ptpns In the Context Of Cancermentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%